Workforce planning and education: Mapping competencies, skills and standards in mental health - Charles Musselwhite (Nurse Education Today, 2006)
This paper aims to identify and critically analyse the provision and commissioning of relevant training for multidisciplinary mental health practitioners in the South West region of England. Data were collected from 45 education and training providers across the region. A total of 132 courses were examined through analysis of a questionnaire and a further 82 courses were studied in more depth through interviews and focus groups, alongside a textual analysis of course documents. Data generated from the analyses were mapped against the competencies and skills outlined in The Capable Practitioner [SCMH, 2001. The Capable Practitioner, Sainsbury Centre for Mental Health, London.] document and National Occupational Standards for Mental Health [Skills for Health, 2004. National Occupational Standards for Mental Health. Available from: <http://195.10.235.25/standards_database/index.htm> (last accessed 17.11.04).]. The findings confirmed that significant gaps exist in training and education. While some aspects of The Capable Practitioner and National Occupational Standards for Mental Health are covered well by courses provided for mental health practitioners in the region, other aspects are missed completely. Recommendations are made for further research, with the suggestion of using an action research and co-operative enquiry method to identify with participants if courses should be developed to cover these areas or if the standards themselves should be adapted. Reflections on the methodological framework and subsequent limitations of the study are outlined.